2018
DOI: 10.1371/journal.pone.0193018
|View full text |Cite
|
Sign up to set email alerts
|

The time-series behavior of neutrophil-to-lymphocyte ratio is useful as a predictive marker in non-small cell lung cancer

Abstract: BackgroundNivolumab improves the survival of advanced non-small cell lung cancer (NSCLC), but a significant number of patients still fail to benefit from this treatment. In this study, we evaluated the efficacy of the time-series behavior of neutrophil-to-lymphocyte ratio (NLR) in a complete blood count from advanced NSCLC patients as a predictive marker of the anticancer effect of nivolumab.MethodsWe performed a retrospective review of medical records and collected data on patients with advanced NSCLC treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 28 publications
3
67
1
2
Order By: Relevance
“…As shown in Figure 2B, the pooled HRs of OS from eight studies 16,18,19,28,30,33,35,36 using random effect model was 1.75(95%CI: 1.33, 2.30), favoring NSCLC patients with low pre-treatment NLR.
10.1080/2162402X.2018.1507262-F0002Figure 2.Comparisons of PFS and OS in Nivolumab treated NSCLC patients with different baseline NLR. A, NLR < cutoff value(low NLR) versus NLR≥ cutoff value(high NLR) for PFS; B, NLR < cutoff value versus NLR≥ cutoff value for OS.
…”
Section: Combined Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…As shown in Figure 2B, the pooled HRs of OS from eight studies 16,18,19,28,30,33,35,36 using random effect model was 1.75(95%CI: 1.33, 2.30), favoring NSCLC patients with low pre-treatment NLR.
10.1080/2162402X.2018.1507262-F0002Figure 2.Comparisons of PFS and OS in Nivolumab treated NSCLC patients with different baseline NLR. A, NLR < cutoff value(low NLR) versus NLR≥ cutoff value(high NLR) for PFS; B, NLR < cutoff value versus NLR≥ cutoff value for OS.
…”
Section: Combined Resultsmentioning
confidence: 98%
“…As there were several studies 16,18,19,28,33,35 set the cutoff value of pre-treatment NLR being 5, we used the value of 5 to find out the influence of different cutoff value on PFS and OS. The studies 16-19,26,28,32,33,35,36 included reported the HRs of high NLR versus low NLR on PFS in the treatment of advanced NSCLC.…”
Section: Combined Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that low baseline NLR and ANC predict the efficacy of nivolumab therapy in various cancers . More recent studies have shown that an early decrease in NLR during treatment with PD‐1 inhibitors predicts its efficacy . NLR and ANC have been reported to correlate with the number of circulating MDSCs and tumor‐associated neutrophils, which suppress the function of antitumor T cells .…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not clarify the mechanisms that created these synergistic effects during nivolumab treatment. Several studies have shown that the neutrophil‐to‐lymphocyte ratio (NLR) and the absolute neutrophil count (ANC) in the blood can predict the efficacy of PD‐1 inhibitors in patients with NSCLC . NLR and ANC have also been reported to reflect the number of circulating myeloid‐derived suppressor cells (MDSCs) and tumor‐associated neutrophils, which inhibit the function of antitumor T cells .…”
Section: Introductionmentioning
confidence: 99%